2022
DOI: 10.24171/j.phrp.2021.0316
|View full text |Cite
|
Sign up to set email alerts
|

Generalized anxiety and sleep quality among health care professionals during the COVID-19 pandemic: a cross-sectional study from a tertiary healthcare institution in Eastern India

Abstract: Objectives: With the emergence of the coronavirus disease 2019 (COVID-19) pandemic, healthcare professionals (HCPs) have experienced high levels of stress and anxiety because of the high risk of infection for themselves and their families. This has led to acute sleep problems for HCP. This study was designed to assess the anxiety and sleep quality of HCPs during the COVID-19 pandemic. Methods: This cross-sectional study analyzed 370 HCPs employed at All India Institute of Medical Sciences Patna over 3 months, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
5
1
2
Order By: Relevance
“…A study by Ahmed M.A et al concluded that 78% of dentists were suffering from fear and anxiety during the pandemic [20]. According to one study, it was discovered that, along with anxiety, healthcare professionals had developed a sleep disorder during the pandemic [21][22][23][24]. This, in turn, was linked to psychological disturbance [22,25].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ahmed M.A et al concluded that 78% of dentists were suffering from fear and anxiety during the pandemic [20]. According to one study, it was discovered that, along with anxiety, healthcare professionals had developed a sleep disorder during the pandemic [21][22][23][24]. This, in turn, was linked to psychological disturbance [22,25].…”
Section: Discussionmentioning
confidence: 99%
“…HCWs who lived in a combined family are two times more likely to display signs of anxiety [ 30 ]. A significant predictor of probable GAD was discovered to be the presence of high-risk family members [ 29 ]. Females are more likely to have anxiety in comparison to males [ 11 , 12 , 17 , 19 , 30 , 44 ] and single people are less likely to be anxious when compared to married people [ 11 , 17 , 37 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Working in primary or secondary healthcare facilities was potentially related to sleep disturbance, although age, educational level, the availability of PPE, and Covid-19 training were not significantly related to sleep pattern [ 37 ]. Significant predictors of low sleep quality included the existence of addictive behaviours, unprotected interaction with COVID-19 individuals, and suspected generalised anxiety disorder [ 29 ]. Sleep quality disturbance was found to be statistically significant with severity of illness as well [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even under normal circumstances, doctors and other healthcare professionals are at increased risk of mental health issues due to the stressful nature of work. The situation was compounded by the pandemic with a high stress level at the workplace leading to depression, anxiety, and panic attacks [ 14 ]. Even some incidents of suicides were reported.…”
Section: Editorialmentioning
confidence: 99%